Novel Prognostic Scores Based on Plasma Prothrombin Time and Fibrinogen Levels in Patients With AFP-Negative Hepatocellular Carcinoma. (24th March 2020) - Mao, Minjie; Wang, Xueping; Song, Yiling; Sheng, Hui; Han, Runkun; Lin, Weihong; Dai, Shuqin
Noninvasive tools for the prognosis of α-fetoprotein negative hepatocellular carcinoma (HCC) are urgently needed. The present study proposed a prognostic system based on preoperative plasma prothrombin time and fibrinogen (PT/Fbg system). With respect to α-fetoprotein (AFP)-negative HCC, we compared the prognostic value in PT/Fbg system, Glasgow Prognostic Score, and aminotransferase/aspartate aminotransferase ratio. The present study retrospectively analyzed patient characteristics, clinicopathological factors, and the level of pretreatment biomarkers in 628 patients with HCC. Patients with increased PT and Fbg levels were allocated a score of 2, patients with only one of these abnormalities were assigned score 1, and patients with neither of these abnormalities were allocated a score of 0. The following distributions of the PT/Fbg system scores were observed: 187 (29.78%) patients had a score of 0, 305 (30.65%) had a score of 1, and 134 (22.69%) patients had a preoperative score of 2. The prognostic significance of the PT/Fbg system was determined using univariate and multivariate Cox hazard analyses in AFP-negative HCC. Multivariate analysis revealed that patients with a higher PT/Fbg system exhibited worse overall survival (OS) than patients with a lower PT/Fbg system. Our study proposes preoperative evaluation of the plasma PT/Fbg system to predict the OS of patients with AFP-negative HCC.